Pharmacokinetic/Pharmacodynamic Evaluation of Dexlansoprazole Infusion Injection Compared with Lansoprazole in Healthy Chinese Adults - Wu, Lihua (Clin Drug Investig, 2019)
BACKGROUND AND OBJECTIVE: This study was performed in healthy Chinese subjects to evaluate the safety and pharmacokinetic/pharmacodynamic characteristics of a novel injection formulation of dexlansoprazole in the context of single and multiple administration, compared with the original lansoprazole injection. METHODS: Helicobacter pylori-negative healthy volunteers were recruited, and 70 participants were enrolled into five dosing groups (seven males and seven females in each group), including 15 mg once daily (qd), 15 mg every 12 h (q12h), 30 mg qd and 30 mg q12h of dexlansoprazole treatment for 5 days, as well as 30 mg q12h of lansoprazole treatment for 5 days. Blood samples were collected at scheduled time spots postdose on day 1 (first dose) and day 5 (last dose). Twenty-four-hour intragastric pH was continuously monitored on day 0 (baseline) and days 1 and 5. Dexlansoprazole and S-lansoprazole in human plasma were determined by validated chiral liquid chromatography with tandem mass spectrometry, and the pharmacokinetic parameters were determined by a non-compartmental method using Phoenix WinNonlin software. Safety assessment included changes in vital signs and laboratory tests, physical examination findings, and incidence or reports of adverse events. RESULTS: The half-life (t(½)) and clearance (CL) of dexlansoprazole were 1.76–2.06 h and 4.52–5.40 L/h, respectively, while the t(½) and CL of S-lansoprazole were 0.87–1.02 h and 34.66–35.98 L/h, respectively. No drug accumulation after repeated administration was noted. Administration of lansoprazole 30 mg resulted in higher area under the concentration-time curve from time zero to the last measurable concentration (AUC(t)) of dexlansoprazole than that of dexlansoprazole 15 mg (p = 0.026). Zero to 24 h after q12h multiple dosing, median and mean intragastric pH, percentage of time with the intragastric pH above 4.0 [TpH ≥ 4.0(%)] and percentage of time with the intragastric pH above 6.0 [TpH ≥ 6.0(%)] in the dexlansoprazole 15 mg q12h group were 6.07 ± 0.61, 5.70 ± 0.76, 83.58 ± 12.34, and 53.70 ± 17.06, respectively, which was similar to the lansoprazole 30 mg q12h group, i.e. 6.15 ± 0.62, 5.88 ± 0.67, 87.26 ± 12.08 and 57.00 ± 16.35, respectively. A weak positive correlation between dexlansoprazole AUC(t) and baseline-adjusted TpH ≥ 4.0(%) over 0–24 h was observed, with Pearson correlation coefficients of 0.437 (p = 0.029), while no correlation was observed between AUC(t) and baseline-adjusted TpH ≥ 6.0(%) over 0–24 h. CONCLUSION: Every 12 h intravenous dosing of dexlansoprazole up to 30 mg for 5 days was safe and well-tolerated in healthy Chinese subjects. Every 12 h dosing of dexlansoprazole 15 mg has a comparable effect of gastric acid inhibition as lansoprazole 30 mg q12h. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT03120273.